Environmental impact on the corrosion behavior of marine grade steel in the Arabian Sea conditions - a comparative analysis of field and laboratory based corrosion tests - Abbas, Muntazir; Simms, Nigel J.; Lao, Liyun; Malik, Owais A.; Ashraf, Luqman (UCTEA Chamber Of Metallurgical and Materials Engineers, 2021)
Corrosion-induced degradation of marine steel structures is highly dependent on the surrounding environmental conditions and so varies significantly around global seawaters. This research has investigated the dependence of corrosion of carbon steel alloy for marine service on seawater composition and climatic conditions typical of the Arabian Sea. Natural and polluted seawater sites in the Arabian Sea were selected for field exposures. In addition, environmental conditions spanning those anticipated for the shipping structures operating in the Arabian Sea have been simulated in laboratorybased experiments by using heated and aerated artificial seawater. Following their exposures, the performance of samples have been investigated using the weight-loss and dimensional metrology methods. High overall corrosion losses were observed in the polluted seawaters than in the natural seawater conditions of Arabian Sea.
Keywords: marine corrosion; Arabian Sea; nitrates; natural seawater; pollutant-rich seawater; artificial seawater